2001
DOI: 10.1089/10926420152389323
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Abdominal Complications in Ventriculoperitoneal Shunt Surgery

Abstract: Ventriculoperitoneal (VP) shunts are among the most frequently performed operations in the management of hydrocephalus. Abdominal complications, though rare, are reported to occur in 5-47%. VP shunt obstruction or malfunction leads to raised intracranial pressure, which requires immediate intervention. Recently we have used the laparoscope to manage abdominal complications of VP shunt in two patients. The first patient had hydrocephalus secondary to tubercular meningitis. She developed recurrent intraabdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The advantages of the laparoscopic approach also include a shorter hospital stay, less post-operative pain, lower chance of incisional hernia formation, and, since the catheter is positioned under direct vision with minimal bowel manipulation, there is a much lower chance of bowel injury and adhesion formation [6,8]. Even when dealing with complications, laparoscopy offers a distinct advantage over laparotomy, especially in terms of superior visualization of the peritoneal cavity, retrieval of displaced shunts, lysis of adhesions, culture of abdominal fluid, repositioning of displaced tubings, and assessing the abdomen for any other pathology [2][3][4]6,8,10]. However, the flip side is that separate incisions (for port and shunt placement) as well as two separate teams (neurosurgical and laparoscopic) are required, which may not be available everywhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of the laparoscopic approach also include a shorter hospital stay, less post-operative pain, lower chance of incisional hernia formation, and, since the catheter is positioned under direct vision with minimal bowel manipulation, there is a much lower chance of bowel injury and adhesion formation [6,8]. Even when dealing with complications, laparoscopy offers a distinct advantage over laparotomy, especially in terms of superior visualization of the peritoneal cavity, retrieval of displaced shunts, lysis of adhesions, culture of abdominal fluid, repositioning of displaced tubings, and assessing the abdomen for any other pathology [2][3][4]6,8,10]. However, the flip side is that separate incisions (for port and shunt placement) as well as two separate teams (neurosurgical and laparoscopic) are required, which may not be available everywhere.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reports by Kausch in the early part of the 20th century of the use of the peritoneal cavity for diverting CSF, ventriculoperitoneal (VP) shunts have become the standard procedure for the treatment of hydrocephalus [1,2]. Like any surgical procedure, VP shunting is also associated with complications; the most common causes of shunt malfunction are proximal obstruction and infection [1] and these usually present with headache, changes in the mental status, and vomiting [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19) Most reported cases of CSF pseudocysts have occurred in children, with only 29 cases in adults. [1][2][3][4][5]7,[11][12][13]15,[17][18][19][20]23) We describe the formation of an abdominal CSF pseudocyst in an adult, and review all 30 adult cases of abdominal CSF pseudocysts. Neurol Med Chir (Tokyo) 52, November, 2012…”
Section: Introductionmentioning
confidence: 99%
“…1,15) The advantages of the laparoscopic approach include shorter hospital stay because of less invasiveness and lower risk of forming postoperative adhesions and related complications compared with laparotomy. 1,15) Infection with Staphylococcus epidermis was detected in 3 of 18 cases examined for bacterial infection (excluding one study 19) in which 4 patients had infections, but were not identified as child or adult). Distal externalization of the peritoneal catheter was performed, antibiotic treatment was administered, and then the distal segment of the shunt tube was replaced in the 3 cases in which infection was detected.…”
mentioning
confidence: 99%